2003
DOI: 10.1109/tbme.2003.808826
|View full text |Cite
|
Sign up to set email alerts
|

AC-coupled front-end for biopotential measurements

Abstract: Abstract-AC coupling is essential in biopotential measurements. Electrode offset potentials can be several orders of magnitude larger than the amplitudes of the biological signals of interest, thus limiting the admissible gain of a dc-coupled front end to prevent amplifier saturation. A high-gain input stage needs ac input coupling. This can be achieved by series capacitors, but in order to provide a bias path, grounded resistors are usually included, which degrade the common mode rejection ratio (CMRR). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(97 citation statements)
references
References 6 publications
0
90
0
7
Order By: Relevance
“…The amplifier circuit used in this work is the 222 instrumentation amplifier circuit described by Spinelli et al 223 which has a gain of 1000 [20]. This amplifier circuit was 224 chosen because it has a high common mode rejection ratio 225 (123 dB at 50 Hz) and contains an AC-coupling element that 226 rejects DC drift at the electrodes.…”
Section: Fabrication Methods 123mentioning
confidence: 99%
“…The amplifier circuit used in this work is the 222 instrumentation amplifier circuit described by Spinelli et al 223 which has a gain of 1000 [20]. This amplifier circuit was 224 chosen because it has a high common mode rejection ratio 225 (123 dB at 50 Hz) and contains an AC-coupling element that 226 rejects DC drift at the electrodes.…”
Section: Fabrication Methods 123mentioning
confidence: 99%
“…1. It consists of AC coupling circuit and three-op amp instrumentation amplifier [1,2]. The ECG detection electrode contains a large DC offset voltage.…”
Section: The Drawback Of Analysis Of the Three-op Amp Approachesmentioning
confidence: 99%
“…The traditional structure ECG readout circuit uses the three-op amp instrumentation amplifier as the main amplifier, while introducing the integral feedback circuit in the system as a DC offset suppression circuit (DSC) to overcome the DC offset and baseline drift [1,2,3,4]. The main drawback of the three-op amp amplifier is: since the intermediate node contains the input common mode voltage, if there is an offset voltage at the input, the input of the second stage cannot eliminate the offset voltage, the output voltage contains the offset voltage amplified by the second stage amplifier.…”
Section: Introductionmentioning
confidence: 99%
“…The bridge output was ac-coupled to a differential amplifier by a fully-differential first-order high-pass filter [17] with cutoff frequency 0.5 Hz, which is high enough to reduce motion artifacts; preliminary tests showed that the frequency components of the J peak were not affected by this filter. The amplifier gain was set to 12,000 and the output was low-pass filtered by a first-order filter with cutoff frequency 100 Hz hence well above the highest frequency components in Figure 2.…”
Section: Signal Acquisitionmentioning
confidence: 99%